2001
DOI: 10.1590/s1517-74912001000100012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the surface treatment of plain carbon fiber posts on the retention of the composite core: an in vitro evaluation

Abstract: This study aims to evaluate the role of surface treatments performed on plain carbon fiber posts, in relation to serrated carbon fiber posts, in the retention of the composite core. Fifty carbon fiber posts received surface treatments in order to verify their influence on the retention of the core material. An acrylic resin mold was developed in order to precisely fit the post, leaving a machined space to accommodate a self-curing composite resin. After the surface treatment, a primer was applied on the corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The durability of a restoration with a composite core depends on the bond between the composite resin and the remaining tooth structure, and also on the bond between the composite core and the fiber post, which helps in stress distribution under functional loading. 8 A variation of composite resin materials, including packable (high elastic modulus), micro hybrid (intermediary elastic modulus) and flowable (low elastic modulus) composites are available for core build-up of endodontically treated teeth. Some laboratory and technical evidence supports the use of flowable composites for restorations reinforced with FRC posts.…”
Section: Introductionmentioning
confidence: 99%
“…The durability of a restoration with a composite core depends on the bond between the composite resin and the remaining tooth structure, and also on the bond between the composite core and the fiber post, which helps in stress distribution under functional loading. 8 A variation of composite resin materials, including packable (high elastic modulus), micro hybrid (intermediary elastic modulus) and flowable (low elastic modulus) composites are available for core build-up of endodontically treated teeth. Some laboratory and technical evidence supports the use of flowable composites for restorations reinforced with FRC posts.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the literature took the form of investigations conducted in vitro. 5,6,[42][43][44][45][46] These studies examined a number of areas such as the physical properties of the posts and post/root relationship, 6,7,9,[12][13][14]20,22,23,[26][27][28][29][31][32][33]35,37,38,42 retention testing, 11,15,19,22,30,[32][33][34]36,43,44 scanning electron microscopy of the post/root interface, 14,16,17,22,38,40,46,47 microleakage, 10,24 and corrosion of metals with fibre-posts. 18 Other papers examined thermal stress, …”
Section: Resultsmentioning
confidence: 99%
“…Surface treatment of smooth carbon-fibre posts with aluminium oxide blasting and grooving with diamond burs has been shown to make core retention comparable with that of the serrated version. 34 Post retention in the root Within the prepared post space, cemented stainless steel posts have been shown to be more retentive than carbon-fibre posts 11,32 when cemented with either resin or zinc phosphate cement. Other workers have however, shown no difference in retention 15,22,44 where posts were cemented with a resin cement.…”
Section: Resultsmentioning
confidence: 99%
“…Over time, it was observed that the use of metal cores was no longer a viable option for many of these cases, due to the absence of adhesion, possibility of corrosion and high modulus of elasticity. 22,23 The prefabricated posts, on the other side, such as those of fiberglass used in the clinical case, were developed to replace in some situations the cast posts and also the prefabricated metal cores. The modulus of elasticity of the fiberglass posts is more similar to dentin, to the resin cement used to fix the post to the tooth and the composite resin to the filling, qualifying it for clinical use.…”
Section: Discussionmentioning
confidence: 99%